First record of Aleuroclava psidii (Singh) and Aleurotrachelus tuberculatus Singh (Hemiptera: Aleyrodidae) in East Africa - Guastella, D.; Tajebe, L.; Evans, G.; Fovo, F.; Rapisarda, Carmelo; Legg, James P. (2014)
Two Asian whiteflies, Aleurotrachelus tuberculatus Singh 1933 and Aleuroclava psidii (Singh 1931), are recorded for the first time in Africa. Both species were found on Psidium guajava L. (Myrtaceae) in the Coast and Dar es Salaam regions of Tanzania. It is not possible to determine when these species might have been introduced, due to the absence of a routine monitoring system for pest introductions in East African countries. However, no records exist of their presence or damage caused to plants in Africa, therefore they have been likely introduced recently. In addition, Aleurodicus dispersus Russell, a widespread, polyphagous whitefly species, was also collected on guava. This species was introduced to Tanzania in 2003 from a putative Asian origin. This fact, coupled with the new introductions reported here, suggests that a pathway exists for the importation of exotic insects or noxious pest species from Asia to East Africa.